Modulation of innate immune responses and induction of oxidative stress biomarkers in Pangasianodon hypophthalmus following an experimental infection with dactylogyrid monogeneans. Issue 63 (April 2017) - Kumar, Saurav; Raman, R.P.; Prasad, K. Pani; Srivastava, P.P.; Kumar, Sanath; Rajendran, K.V.
Abstract: Modulation of innate immune activity and oxidative stress response of Pangasianodon hypophthalmus through experimental infection with ( Thaparocleidus sp.) dactylogyrid monogenean was studied. A standard cohabitation method was used to infect healthy experimental fish. After 14 days, dactylogyrid (gill monogenean) infested fish were sampled and categorised into three different infected groups namely (T1) low (<10 mean dactylogyrid per gill arch per fish), (T2) moderate (10–49 mean dactylogyrid per gill arch per fish) and (T3) high (>50 mean dactylogyrid per gill arch per fish) along with a control group T0 (un-infested fish). Serum and tissues (gills and liver) were collected from experimental fish and analyzed for markers of innate immune and oxidative stress, respectively. The results showed that respiratory burst activity, myeloperoxidase level, serum lysozyme, α-2 macroglobulin and total serum immunoglobulin level were significantly (p < 0.05) elevated in fish with different degrees of parasite infestation compared to the control (un-infested group). Similarly, cellular oxidative biomarkers superoxide dismutase, catalase, glutathione-S-transferase and Na + -K + -ATPase activities of gills and liver were significantly (p < 0.05) elevated in dactylogyrid infested fish in comparison to the control. However, significantly decreased level of albumin, albumin to globulin ratio, total serum antiprotease and ceruloplasmin were observed in fish infested with low degree of dactylogyrids, while no significant differences in these parameters were observed between moderately infested and the control groups. The results suggested that varying degree of gill monogenean dactylogyrid infestation not only modulated the innate immune response of P. hypophthalmus by lowering albumin, total serum antiprotease and ceruloplasmin and inducing respiratory burst activity, phagocytic activity, myeloperoxidase, lysozyme, α-2 macroglobulin and total immunoglobulins, but also the oxidative stress biomarkers. The baseline data obtained in the present study will be valuable in understanding the host-parasite relationship and the dynamics of innate, oxidative stress responses and susceptibility of P. hypophthalmus to different degrees of parasitosis. Highlights: Innate immune responses in P. hypophthalmus were studied under various degrees of dactylogyrid infection. Moderate and high dactylogyrid loads suppress ceruloplasmin and serum antiprotease activity. Oxidative stress biomarkers in P. hypophthalmus were induced under various degrees of dactylogyrid infection. Higher dactylogyrid load induces GST and Na + -K + -ATPase activity in gills and liver.